Developments in preparation and dyeing of CORONA discharged cellulosic materials - Carneiro, Noémia (2005)
The preparation and dyeing of cellulosic fabrics hás important problems such as uniformity of aspect, cleaning efficiency, level of bleaching, conformity and fastness of colours, and ecological impact. Combination of preparation processes can give optimal solutions, regarding economy and ecology, especially if superior quality items are achieved in final products. In fact, high standards concerning whiteness, starch removal and hidrophilicity are considered a good basis for leveled, cleaner and intense dyeing. A better white basis, escellent hidrophilicity and enough removal of impurities are obtained if desizing is omitted and a CORONA discharge is made over dry grey material. Exhaustion dyeings with different classes of direct dyes show similar behavior concerning the positive influence of the discharge in the intensity of colours and their fastness. Good penetration of dyes in coronised cotton materials is assured and consequently a good fastness is abtained.